2022
DOI: 10.3390/su142113965
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Influencing Urban and Rural Area students to Use Tablet Computers as Learning Tools: Combination of UTAUT and TTF Models

Abstract: University students use various ICT-based media a goal to help them learn. The Chinese government is also increasing the use of ICT tools in the education sector because they relate to university students’ learning outcomes. Several universities in China provide tablet computer facilities as learning tools for their university students. These learning tools are widely used in the country because they have many benefits in educational settings. For instance, they are paperless, practical, and portable and suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…For instance, Zhou et al, [ 46 ] hypothesize that TAC and TEC have a positive effect on TTF. The prior research has a strong foundation for the link between TAC, TEC, and TTF, as shown by publications by Afshan and Sharif [ 50 ], Wang et al [ 51 ], and Wang et al [ 52 ]. The ensuing hypotheses have been established as a result.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…For instance, Zhou et al, [ 46 ] hypothesize that TAC and TEC have a positive effect on TTF. The prior research has a strong foundation for the link between TAC, TEC, and TTF, as shown by publications by Afshan and Sharif [ 50 ], Wang et al [ 51 ], and Wang et al [ 52 ]. The ensuing hypotheses have been established as a result.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Students also appreciate paperless activities. Switching to paperless activities turned out to be a practical support to students [27].…”
Section: Student Conveniencementioning
confidence: 99%
“…Recently, scholars have claimed that the PV of mobile delivery food services plays a vital role in formulating attitudes (Gupta and Duggal, 2021;Sharma et al, 2021). If customers perceive the high value of services or food products as a result of low expenses and high benefits when using the FDA, they will have a more favorable attitude towards the given app (Wang et al, 2022a(Wang et al, , 2022b. Thus, in the FDAs business setting, we propose the following hypothesis:…”
Section: Perceived Valuementioning
confidence: 99%
“…To better understand customer behavior towards the continued use of FDAs, three factors, namely, TTF, PV and perceived food safety, were added to the original TCT model. Several studies on technology adoption have found that TTF is the most important driver of users’ perceptions of and behaviors towards technology (Gupta et al , 2022; Wang et al , 2022a, 2022b). Zhao and Bacao (2020) supported the importance of the TTF in the FDA context.…”
Section: Literature Reviewmentioning
confidence: 99%